Mean-Field Modeling of Green Technology Adoption: A Competition for Incentives - Luca Grosset; Elena Sartori (Mathematics)
This paper investigates the role of fiscal incentives in promoting the transition to a green economy using a dynamic mean-field game framework. By modeling firms as representative agents undergoing an environmentally sustainable transition, we analyze two distinct types of incentive structure: fixed incentives and incentives based on the average behavior of firms. The findings underscore the importance of balancing incentive structures to avoid economic inefficiencies and ensure a smooth ecological transition.